Divergence equations and uniqueness theorem of static spacetimes with conformal scalar hair. (20th August 2021) - Shinohara, Takeshi; Tomikawa, Yoshimune; Izumi, Keisuke; Shiromizu, Tetsuya
Abstract: We reexamine the Israel-type proof of the uniqueness theorem of the static spacetime outside the photon surface in the Einstein-conformal scalar system. We derive in a systematic fashion a new divergence identity which plays a key role in the proof. Our divergence identity includes three parameters, allowing us to give a new proof of the uniqueness.